2007
DOI: 10.1007/s00044-007-9049-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of the 5-fluorouracil-pectin conjugate targeted at the colon

Abstract: This paper describes the first covalent synthesis of a 5-fluorouracilpectin (FU-PT) conjugate. This conjugate with the potential for colon-targeted delivery has been evaluated. A sensitive high-performance liquid chromatography (HPLC) method was established for the determination of concentration of 5-FU-1-acetic acid in the gastrointestinal contents and plasma of rats. This method was also used to evaluate the colon-targeting properties of 5-FU-PT. 5-FU-PT was given to rats by oral administration at a dosage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 8 publications
(6 reference statements)
0
5
0
1
Order By: Relevance
“…A variety of chemically modified 5-FU derivatives have been synthesized to enhance their antitumor efficacy 48 , 49 , but their irregular oral absorption, low bioavailability and lack of specificity often result in poor clinical therapeutic outcomes 5 – 7 . In order to improve the oral bioavailability, a wide variety of polymers have been synthesized for direct or indirect attachment of 5-FU and its derivatives 50 , 51 . In the present study, 5-FA was introduced as a 5-FU derivative as it has been reported to be highly effective and less toxic 52 .…”
Section: Discussionmentioning
confidence: 99%
“…A variety of chemically modified 5-FU derivatives have been synthesized to enhance their antitumor efficacy 48 , 49 , but their irregular oral absorption, low bioavailability and lack of specificity often result in poor clinical therapeutic outcomes 5 – 7 . In order to improve the oral bioavailability, a wide variety of polymers have been synthesized for direct or indirect attachment of 5-FU and its derivatives 50 , 51 . In the present study, 5-FA was introduced as a 5-FU derivative as it has been reported to be highly effective and less toxic 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The gelation mechanism of pectins is mainly governed by their DE. For the LM pectins, denoted LMP (DE<50%), gelation results from specific non-covalent ionic interactions between blocks of galacturonic acid residues of Pectin as a carrier for novel drug delivery 5FU-Pectin conjugates [25] 5-Fluorouracil 5-FU-PT conjugate has a good colon-targeting property Pectin-Ketoprofen prodrug [23] Ketoprofen Irritation effect of KP of GI membranes may reduce by the conjugation with PT because of esterification of the KP with PT thus enzyme-dependent PT-KP prodrug with pectin as a carrier Microsphere [20,26] Indomethacin Pectin microsphere degraded by pectinase that is found in the colon and as a result, IND release was increased Beads [27,28] Indomethacin Drug showed very little release (less than 5%) of the drug to the SGF and the rate of release decrease with increase in the concentration of pectin Microsphere [29] Indomethacin and tetracycline Give importance about various parameters like polymer, drug, CaCl 2 , emulsifier concentration and stirring speed seen as type of polymer and emulsifier Hydrogel beads [30,31] Indomethacin or Sulfamethoxa-zole Amidated pectins are more tolerant to pH variations, which is useful in colonic delivery systems Pectin as a carrier for conventional drug delivery Capsule [32] Ketoprofen Zinc pectinate beads showed slower ketoprofen release compared with calcium pectinate beads when enteric hard capsules were used. Thus, the zinc pectinate beads could protect sufficiently drug entrapped from the upper gastrointestinal conditions and drug release will be controlled by pectin degradation with colonic microflora Matrix tablets [33] Ropivacaine Reduce the release of the drug in simulated gastric and intestinal fluids, increase the release in simulated caecal fluid (with pectinolytic enzymes), and improve the poor compactibility of pectins Matrix tablets [11] Indomethacin Better in vitro release of water-insoluble drug using calcium salt as cross-linker Enteric-coated matrix tablets [18] -Enteric-coated matrix tablets of pectin arrive intact in the colon where complete disintegration and release occurred compared to the guar gum tablet Matrix tablets [34] Paracetamol In vitro trials have confirmed that increasing the coating layer reduced drug release Compression-coated tablet [34] Naphthol Green B NGB rapidly released from the pectin-coated tablet in the presence of enzymes compared with the control Compression-coated and plain matrix tablet [19] Indomethacin and insulin Selective drug targeting to the colon due to presence of pectinolytic enzymes Compression-coated tablet [15] Sodium fluorescein Compression coat of pectin protecting a core tablet in stimulating gastrointestinal environment Compression-coated tablet [35]…”
Section: Gelation Of Pectins Low Methoxy Pectinmentioning
confidence: 99%
“…These observations suggest the design of an isostructural CP to improve the cytotoxic activity, in which the difference is the substitution of uracil-1-acetate by 5-fluorouracil-1-acetate as the terminal ligand since 5-fluorouracil-1-acetate is a derivative of the essential anticancer agent 5-FU . The new CP2n presents a similar behavior in the biological media to that of CP1n .…”
Section: Discussionmentioning
confidence: 88%